2019
DOI: 10.1016/j.marenvres.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes on estuarine ciliates linked with modifications on wind patterns and water turbidity

Abstract: Highlights ► Planktonic ciliate's abundance decreased over the last 25 years in a shallow estuary. ► Decreasing cell abundance was linked to changes in wind dominant regimes and increased water turbidity. ► Tintinnids were more vulnerable to wind patterns and turbidity and lost synchrony with primary productivity. ► Interannual variability of the copepod Acartia tonsa followed the changes in ciliate community. ► Erosive processes in shallow estuaries impact on the interannual dynamics of ciliates and such effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
1
2
1
Order By: Relevance
“…In addition, the turbidity of pond water fluctuated slightly (1.39–3.74 NTU) (Fig. 2 d), possibly due to the presence of strong seasonal wind, similar to observation reported by previous researchers 50 . Figure 2 e represents the total daily rainfall at the site of the natural outdoor pond throughout the four weeks of observation interval.…”
Section: Resultssupporting
confidence: 90%
“…In addition, the turbidity of pond water fluctuated slightly (1.39–3.74 NTU) (Fig. 2 d), possibly due to the presence of strong seasonal wind, similar to observation reported by previous researchers 50 . Figure 2 e represents the total daily rainfall at the site of the natural outdoor pond throughout the four weeks of observation interval.…”
Section: Resultssupporting
confidence: 90%
“…In general, the abundance of ciliates varied substantially across the study period at the Jiulong River estuary sampling site, with a narrow gradient of high estuarine salinities. In comparison to other coastal estuaries and bays worldwide (Chiang et al, 2003;Strom et al, 2007;Tsai et al, 2011;Haraguchi et al, 2018;Loìpez-Abbate et al, 2019;Yang et al, 2020;Gu et al, 2021), the abundance of ciliates was comparatively lower, ranging between 0 and 95 cells l −1 , although this was within the range reported in some literature (Santoferrara and Alder, 2009;Santoferrara et al, 2010). Additionally, due to the small number of sampling stations (1 station) and the short sampling period (6 days), only 13 ciliate species were recovered, far fewer than in previous largearea sampling studies in the estuary (Tsai et al, 2011;Yang et al, 2020;Gu et al, 2021).…”
Section: High Dynamics Of Ciliate Assemblagescontrasting
confidence: 56%
“…Typically, the abundances of microbial members change considerably between measured time points (Gonze et al, 2018). For example, monthly or interannual time-series studies have shown that the abundance of ciliates in the Bahía Blanca Estuary can fluctuate by an order of magnitude, and wind-induced processes and water turbidity are responsible for ciliate dynamics (Loìpez-Abbate et al, 2019). While these studies yielded valuable insights into the longterm dynamics of ciliates, they could be easily obscured by the strong seasonal variations, particularly in the case of an uneven sampling distribution and subsequent inaccuracies.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of regional microzooplankton derives from investigations further south in Argentinean waters (Thompson et al ., 1999; Thompson and Alder, 2005; Santoferrara and Alder, 2009), including the Patagonian shelf (Antacli et al ., 2018), the Beagle Channel (Barría de Cao et al ., 2013) and the Bahía Blanca estuary (Barría de Cao et al ., 2005, 2011; Pettigrosso and Popovich, 2009; López-Abbate et al ., 2015, 2019). Further observations are available for Brazilian coastal and shelf waters (Eskinazi-Sant'Anna and Björnberg, 2006; Islabão and Odebrecht, 2011; Gonçalves-Araujo et al ., 2018; Menezes et al ., 2019), and Patos Lagoon estuary (Jesus and Odebrecht, 2002).…”
Section: Introductionmentioning
confidence: 99%